HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN DISIPLIN KERJA GURU DI SEKOLAH MENENGAH KEJURUAN NEGERI (SMK N) KOTA SOLOK - Ananda Vitra Nola (Universitas Negeri Padang, 2014)
This type of research is descriptive and research korelational.Populasi are all teachers in SMK Kota Solok with number 210. A large sample of 72 people who are determined by proportional stratified random sampling technique. The research instrument was a questionnaire Likert scale models that have been tested for validity and reliability. Data were analyzed using product moment correlation technique. The results of the data analysis showed that: leadership in SMK Kota Solok are in enough categories (69.4%) and work discipline teacher in SMK Solok in the category Low (63%). There is a significant and positive relationship between Leadership at Work Discipline Teacher at SMK Kota Solok with correlation coefficients at the level of 95% with a count r = 0,288 > r table = 0.284. From these results it can be concluded that leadership is one of the factors that influence. Key word: Kepemimpinan dan Disiplin Kerja